Applications of the Heck reaction for the syntheses of substituted pyridines and β,β-disubstituted vinyl Weinreb amides: studies towards the syntheses of inthomycin B and inthomycin C - Baker, D (2014)
The Heck reaction has become a fundamental reaction for synthetic organic chemists over the last half century and is utilised heavily in the fine chemical industry and for natural product synthesis. This thesis describes some of the applications of the Heck reaction to modern day organic synthesis. Introduction: This section presents an overview of the Heck reaction starting from its conception during the late 1960s to present day understanding. A variety of ligand classes are described along with commonly accepted catalytic cycles for their activity during the reaction. Results and Discussion: In the first part of the thesis, the use of a cross-metathesis/Heck reaction protocol to synthesise a range of 2,4,6-trisubstituted pyridines is described. Attempts were made to expand the scope of the methodology by employing vinyl Weinreb amides, but this proved unsuccessful for the synthesis of pyridines. Nevertheless, the Heck reaction on vinyl Weinreb amides worked efficiently and the scope of this arylation was explored. Following on, the functionalisation of the Weinreb amide products was studied to generate a range of enone products, some of which would be difficult to synthesise via direct Heck reaction on the respective precursor enone. In the second part of the thesis, previous syntheses of inthomycin B and inthomycin C are described. The synthesis of inthomycin B and inthomycin C were then attempted using an unprecedented Mukaiyama aldol/cross-metathesis based approach to generate the triene core of both natural products.